1996
DOI: 10.1002/(sici)1099-1573(199603)10:2<145::aid-ptr793>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Neuropharmacological Studies on Ethanol Extracts ofValeriana officinalisL.: Behavioural and Anticonvulsant Properties

Abstract: An ethanol total extract of the roots of Valeriana officinalis L. in doses equivalent to 0.5–800 mg valerian root/kg b.w.i.p. was tested in male mice for possible neuropharmacological efficacy and in this respect compared with diazepam and haloperidol. The extract did not modify spontaneous motility, nociception or body temperature, and did not produce palpebral ptosis. However, it was anticonvulsant against picrotoxin (but not pentetrazol and harman) with an ED50 between 4.5 and 6 mg/kg and it prolonged thiop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
1
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 16 publications
0
51
1
1
Order By: Relevance
“…V. officinalis has been longley used as an important source of pharmaceutical compounds in traditional medicine (Straube, 1968;Morazzoni and Bombardelli, 1995;O'Hara et al, 1998) e.g., clinical trials have shown that valerian extract is effective in treatment of mild to moderate sleeping disorders and it can encourage sleep and improve sleep quality (Leathwood and Chauffard, 1985;Schulz et al, 1994). Furthermore, the valerian root is considered as mild anodyne, anticonvulsant, antispasmodic, carminative and hypotensive (Capasso and DeFeo, 1996;Hiller, 1996). Potential mechanisms for the pharmacological activity of valerian extracts may include increased release of γ-aminobutyric acid (GABA) and agonistic activities on the GABA receptors (Marder et al, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…V. officinalis has been longley used as an important source of pharmaceutical compounds in traditional medicine (Straube, 1968;Morazzoni and Bombardelli, 1995;O'Hara et al, 1998) e.g., clinical trials have shown that valerian extract is effective in treatment of mild to moderate sleeping disorders and it can encourage sleep and improve sleep quality (Leathwood and Chauffard, 1985;Schulz et al, 1994). Furthermore, the valerian root is considered as mild anodyne, anticonvulsant, antispasmodic, carminative and hypotensive (Capasso and DeFeo, 1996;Hiller, 1996). Potential mechanisms for the pharmacological activity of valerian extracts may include increased release of γ-aminobutyric acid (GABA) and agonistic activities on the GABA receptors (Marder et al, 2003).…”
Section: Introductionmentioning
confidence: 97%
“…In a similar way, the A. copa aqueous extract-like low doses of DZ present an anxiolytic effect at doses (0.5 g/kg) that do not produce a decrease in the activities evaluated in the SMA and hole-board tests. The increase in locomotor activity is a consequence of the anxiolytic effect produced by low doses of A.copa and diazepam (Hiller & Zetler, 1996).…”
Section: Discussionmentioning
confidence: 97%
“…The observations were made without prior knowledge of the experimental conditions applied to the animal. Reduced exploratory rearing showed by naïve mice after placement in an unfamiliar environment reveals a sedative effect (Hiller & Zetler, 1996;Oliva et al, 2004;Rolland et al, 1991;Ugalde et al, 2005).…”
Section: Sedative Activity In the Exploratory Cylinder Testmentioning
confidence: 99%